Rise of the Colorado Plateau: A Synthesis of Paleoelevation Constraints From the Region and a Path Forward Using Temperature-Based Elevation Proxies - Heitmann, Emma O.; Hyland, Ethan G.; Schoettle-Greene, Philip; Brigham, Cassandra A. P.; Huntington, Katharine W. (Frontiers in Earth Science, 2021)
The Colorado Plateau’s complex landscape has motivated over a century of debate, key to which is understanding the timing and processes of surface uplift of the greater Colorado Plateau region, and its interactions with erosion, drainage reorganization, and landscape evolution. Here, we evaluate what is known about the surface uplift history from prior paleoelevation estimates from the region by synthesizing and evaluating estimates 1) in context inferred from geologic, geomorphic, and thermochronologic constraints, and 2) in light of recent isotopic and paleobotanical proxy method advancements. Altogether, existing data and estimates suggest that half-modern surface elevations were attained by the end of the Laramide orogeny (∼40 Ma), and near-modern surface elevations by the mid-Miocene (∼16 Ma). However, our analysis of paleoelevation proxy methods highlights the need to improve proxy estimates from carbonate and floral archives including the ∼6–16 Ma Bidahochi and ∼34 Ma Florissant Formations and explore understudied (with respect to paleoelevation) Laramide basin deposits to fill knowledge gaps. We argue that there are opportunities to leverage recent advancements in temperature-based paleoaltimetry to refine the surface uplift history; for instance, via systematic comparison of clumped isotope and paleobotanical thermometry methods applied to lacustrine carbonates that span the region in both space and time, and by use of paleoclimate model mediated lapse rates in paleoelevation reconstruction.